Reading interests, reading habits and information needs of the urban poor in Constitution Hills, Quezon City a survey with the implication for providing library services for them - Viray, Jacoba de Guzman 1948-
Almost 100 precent of the respondents have reading materials in their homes consisting of newspapers, books and comics magazines. Reading on a once a week basis is high for the residents. The adults read more frequently and they have used library facilities more often than the youngsters.